Invasive Plants: Ecological and Agricultural Aspects
DOI: 10.1007/3-7643-7380-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Importance of species replication in understanding plant invasions into North American grasslands

Abstract: The global homogenization of the Earth's biota is expected to increase due to the increase in movement of people and goods between regions, and many introduced species are having a negative economic impact. The increase of introduced species can be thought of as a major global change, because ecosystems throughout the world are now impacted by exotics [1,2]. Grasslands, which cover roughly 25% of the globe, contain perhaps the most disrupted and homogenized communities in the world. Native grasslands have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 46 publications
(77 reference statements)
1
16
0
Order By: Relevance
“…Variation among species within groups can also complicate interpretation of paired species experiments, where diVerent outcomes (e.g., native > introduced, native = introduced, or native < introduced) are possible between pairs solely due to the variation among species within each group (Wilsey 2005). For example, Wilsey (2005) reanalyzed the data presented by Daehler (2003) and found that in replicated studies aboveground biomass was higher for introduced than for native species much more frequently than in nonreplicated studies (Wilsey 2005).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Variation among species within groups can also complicate interpretation of paired species experiments, where diVerent outcomes (e.g., native > introduced, native = introduced, or native < introduced) are possible between pairs solely due to the variation among species within each group (Wilsey 2005). For example, Wilsey (2005) reanalyzed the data presented by Daehler (2003) and found that in replicated studies aboveground biomass was higher for introduced than for native species much more frequently than in nonreplicated studies (Wilsey 2005).…”
Section: Discussionmentioning
confidence: 92%
“…A potential problem with many published comparisons is that they do not replicate species within each introduced or native group, and the lack of replication may have been responsible for the lack of a signiWcant diVerence in the review of Daehler (2003), which was based on a tally of results as native > exotic, native = exotic, or native < exotic. Wilsey (2005) found that only 16% of studies in which native and introduced species were compared included replication, and that conclusions about exotic-native diVerences varied between replicated and unreplicated data sets. Paired species (i.e., one native and one introduced species) studies are directly relevant only in ecosystems where monocultures are common, such as salt marshes (e.g., Callaway and Josselyn 1992).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Numerous previous studies have tested the hypotheses that exotic species are more productive or competitive than native species (reviewed by Daehler 2003;Vila and Weiner 2004;Wilsey 2005;Liao et al 2008). However, it has been difficult to infer general differences between native and exotic species because many previous studies have compared exceptionally competitive exotic invasive species to relatively weak native competitors, or failed to consider numerous confounding environmental variables (reviewed by Daehler 2003;Vila and Weiner 2004;Wilsey 2005;Liao et al 2008). Common garden grassland experiments that have carefully paired native and exotic species have found that exotic species can be more productive than native species (Wilsey and Polley 2006;Wilsey et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Aboveground net primary productivity has been one of the most commonly considered ecosystem functions in grazing studies (reviewed by Milchunas and Lauenroth 1993;Asner et al 2004), native-exotic species comparisons (reviewed by Daehler 2003;Wilsey 2005), and biodiversity experiments (reviewed by Balvanera et al 2006), in part because it integrates across numerous ecosystem functions at multiple trophic levels (McNaughton et al 1989). Root biomass is also important because it is often a considerable fraction of the total biomass in grasslands (e.g., Reich et al 2001;Wilsey and Polley 2006).…”
Section: Introductionmentioning
confidence: 99%